Healthcare Priorities for Surgical Care in Canada - Kaitlyn Squires, BSc; Mercedes Pilkington, MD; Louise Clément, MD; Mary E. Brindle, MD (Annals of Surgery Open)
Surgical disease is one of the most costly and morbid areas of health care and, perhaps, the most amenable to improvement through well-designed and well-implemented tools. Preventable adverse events have been successfully targeted by tools such as the Surgical Safety Checklist. However, health system priorities related to surgery have evolved; the concepts of what constitutes quality care have changed over time. How efficiency and access contribute to safe care, where equity exists as a key outcome measure, and the central role of the patient in defining good care have changed the way we look at surgical priorities. This review of Canadian surgical priorities provides a unique perspective on how we should consider national strategies for surgical safety by exploring both nationally published data as well as the priorities set by provincial and governmental agencies that extend beyond traditional clinical metrics.